Spirituality and social care : contributing to personal and community well-being - Nash, Mary, 1946-; Stewart, Bruce, 1951- (Jessica Kingsley Publishers, 2002)
This comprehensive and much-needed resource is for professionals and students in social care, who are required to engage with the spiritual dimension of their therapeutic work with clients. The authors, who include social workers, mental health professionals, religious professionals and academics, show how they have developed ways of applying their own and their clients' spirituality in their practice. They describe their work in an international range of human service contexts including: * working with grief and loss * community development work * working across cultures * social justice work.